Model Komunikasi Dakwah Berbasis Humanity di Era Digital: Upaya Transformasi Nilai-nilai Islam Rahmatan Lil Alamin - Muhamad Basyrul Muvid (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2023)
Digitalization is progress and also a problem in life, because with technological facilities the spread of Islamic da'wah is designed with an extreme understanding. Therefore, the purpose of this research is to find alternative da'wah models that can balance these extreme da'wah, so that a humanity-based da'wah communication model was initiated. The method used is literature study with interpretive analysis techniques. The results obtained are that the humanity-based da'wah communication model is based on the goals of Islam as a religion of mercy, so that the da'wah carrier adjusts to the vision and mission of Islam itself, namely with a humanistic, humorous, ethical and interactive approach that succeeds in anesthetizing the community (jamaah) into a moderate paradigm, open and tolerant so that they can accept all the differences that exist in their lives without questioning them. Figures that can be used as a reference in implementing a humanity-based da'wah communication model are Gus Baha, Gus Miftah and Gus Muwafiq, all three of whom always spread Islam in a friendly and contextual approach so that it is easily accepted among the general public.